Creating Shared Value to Get Social License to Operate in the Extractive Industry : a Framework for Managing and Achieving the Social License to Operate - Saenz, Cesar (Emerald points., 2021)
Creating Shared Value to get Social License to Operate in the Extractive Industrypresents techniques and models that will enable you to actually formulate, implement, and evaluate strategies to shared value to earn SLO.